Transformation of Markets and Policy Instruments for Open Market Operations - Axilrod, S. (IMF Working Papers; Working Paper ;, 1995)
As developing countries and economies in transition have relied on deregulated, competitive markets to spur growth, their central banks have shifted toward using open market operations as a tool of monetary policy. To be most effective, such operations require supportive changes in other policy instruments (reserve requirements, discount window), a competitive banking system and securities market, and adaptation of particular open market or market-type instruments used to the stage of, and potential for, market development. The paper assesses options available to a central bank for encouraging a competitive market architecture and designing instruments for implementation of open market operations.